Growth of Japan-U.S. Cross-Border Investments in the Electronics Industry - Serapio, Manuel G. Jr (Research management (Now: research technology management))
Manuel G. Serapio, Jr. examines the reasons for the dramatic growth in the number of R&D facilities that each country has established in the other since 1985.